Supply Chain Resilience Design Using Quality Function Deployment Approach - Wardani, Risma Dwi Sukma; Ernawati, Dira; Nugraha, Isna (Academia Open, 2026)
General Background: Supply chain resilience is essential for maintaining operational continuity, service reliability, and competitiveness when manufacturing firms face uncertainty and disruption. Specific Background: A woven bag and jumbo bag manufacturing context experienced supply chain problems involving product returns, demand fluctuation, defective products, distribution disruption, and raw material delivery delays. Knowledge Gap: Previous supply chain resilience studies have often examined risks, causes, or mitigation strategies separately, while integrated models linking customer needs, risk priorities, risk causes, and resilience measures remain limited. Aims: This study aimed to design a supply chain resilience strategy using Quality Function Deployment through a three-level House of Quality framework. Results: The analysis identified 20 customer needs, 18 potential risks, 25 risk causes, and 25 resilience measures. HOQ 1 ranked product return as the highest risk, followed by demand fluctuation, defective products, distribution disruption, and raw material delivery delays. HOQ 2 identified operation negligence, inaccurate demand forecasting, SOP parameter mismatch, suboptimal distribution planning and control, and supplier delivery delays as the main causes. HOQ 3 prioritized employee training, production planning, preventive maintenance, supplier collaboration, and supplier risk management. Novelty: This study integrates supply chain resilience and QFD through layered HOQ analysis. Implications: The findings support risk-based planning, supplier coordination, workforce capability development, and more resilient supply chain management. Highlights: Product return ranked first among operational disruptions. Operation negligence became the highest ranked causal factor. Employee training became the primary mitigation action. Keywords: Supply Chain Resilience, Quality Function Deployment, Risk Management, Supply Chain, Resilience Measures